Determination of Royalty Rates for International Technology Transfer Agreements - Kapitsa, Yu.; Aralova, N. (Science and Innovation, 2024)
The existing approaches used for setting the royalty rates for technology transfer agreements and based on the experience of research institutions of the National Academy of Sciences of Ukraine, research organizations and universities in Europe and USA have been reviewed. The existing rates have been analyzed; recommendations on setting the royalty rates for technology transfer agreements between research institutions and foreign and domestic partners have been elaborated.